Sea‐surface emissivity parametrization from microwaves to millimetre waves. (14th December 2016) - Prigent, C.; Aires, F.; Wang, D.; Fox, S.; Harlow, C.
Abstract : In preparation for new observations on board the next generation of the European operational meteorological satellite ( EUMETSAT Polar System—Second Generation ( EPS‐SG )), a parametrization of the sea‐surface emissivity is proposed from 10–700 GHz: Tool to Estimate Sea‐Surface Emissivity from Microwaves to sub‐Millimeter waves (TESSEM 2 ). It is based on the community model FAST microwave Emissivity Model (FASTEM) at frequencies up to 200 GHz, where FASTEM has been calibrated and validated operationally. It follows a physical emissivity model at higher frequencies. A preliminary evaluation of TESSEM 2 has been conducted with success, by comparison with airborne International Sub‐Millimetre Airborne Radiometer (ISMAR) observations from 118–325 GHz, under low wind speed (3–5 m s −1 ) off the coast of Scotland. TESSEM 2 is a fast parametrization that can easily be implemented in a community radiative transfer model. The code is available to the community and will be distributed with the next version of Radiative Transfer for the TIROS Operational Vertical Sounder (RTTOV).